Inventarisasi Jamur Basidiomycota di Hutan Batu Tikar Kecamatan Luwuk Kabupaten Banggai - Anggo, Sulasmi; Nurlia, Nurlia; N Puwa, Mirdawati (bionature, 2021)
Abstract. There are many kinds of fungi in nature, both macroscopic and microscopic. One of the macroscopic fungi is Basidiomycota. This study aims to determine the results of an inventory of the Basidiomycota mushroom species in the BatuTikar Forest, Luwuk District, Banggai Regency. This type of research is an exploratory descriptive which was conducted from July to August 2020 in Batu Tikar Forest, Luwuk District, Banggai Regency. The population was all types of fungi and the research sample was the Basidiomycota mashroom. This research used cruise method. Data collection techniques are data collected based on secondary data, namely data obtained directly by researcher in the form of photos or other sources. The data analysis technique used a descriptive qualitative analysis by describing the types of fungi based on the morphological characteristics of the types of fungi that had been found in the research location. The results showed that the Basidiomycota mashroom found in the Batu Tikar Forest, Luwuk District, Banggai Regency were 43 types of mushrooms, from 15 families. The dominant families were the Polyporaceae and the Ganodermataceae family, while the least family were Marasmiaceae, Tricholomaticeae, Agaricaceae, Mycenaceae, Psathyrellaceae, Fomitopsidaceae, Bondarzewiaceae, Amanitaceae, Dacrymycetaceae, Steraceae, Auriculariaceae, Hymenochaetaceae, dan Poriaceae.Â Keywords: inventory, basidiomycota mushroom.